2013
DOI: 10.3174/ajnr.a3764
|View full text |Cite
|
Sign up to set email alerts
|

Diffusional Kurtosis Imaging of the Developing Brain

Abstract: BACKGROUND AND PURPOSE:Diffusional kurtosis imaging is an extension of DTI but includes non-Gaussian diffusion effects, allowing more comprehensive characterization of microstructural changes during brain development. Our purpose was to use diffusional kurtosis imaging to measure age-related microstructural changes in both the WM and GM of the developing human brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
91
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 31 publications
9
91
0
Order By: Relevance
“…These results are consistent with a rapid increase in FA and MK measured in the early years of life (Paydar et al, 2014). The changes in intra-axonal water fraction and tortuosity likely result from active myelination, via the reduction of the extra-axonal space, and not from an increase in number of axons.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are consistent with a rapid increase in FA and MK measured in the early years of life (Paydar et al, 2014). The changes in intra-axonal water fraction and tortuosity likely result from active myelination, via the reduction of the extra-axonal space, and not from an increase in number of axons.…”
Section: Discussionsupporting
confidence: 90%
“…Changes in DTI and DKI metrics with age and development have been reported elsewhere on this pool of children (Paydar et al, 2014). Briefly, Figure 2 shows quantitative maps of DTI and DKI metrics in a 9 day old male and in a 323 day old male.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Indeed, in the same way as experiential values between 0.15 to 0.25 are used for the FA threshold, values between 0.7 and 0.8 for MK LHM can be recommended for a simplified application of the D-KIT in the whole brain of the middle-aged adults. In children [76] and eventually, in very elderly adults [4], MK values may depend on the age more strongly, therefore, more differentiated approach would be required. Alternative approaches to determine optimal low MK threshold can involve using percentile analysis of MK histograms.…”
Section: Discussionmentioning
confidence: 99%
“…To briefly summarize, studies have shown DKI to have potential in diagnostics of a number of diseases such as stroke [4,5], Alzheimer's disease [6], multiple sclerosis [7], gliomas [8,9], and head trauma [10][11][12] (see also the review of this area in Ostergaard et al [13]). DKI is not only of clinical interest but is also a valuable tool in basic neuroscience, and the method has for example been employed in studies of natural alteration of brain microstructure e.g., in the context of development and aging [14,15].…”
Section: Introductionmentioning
confidence: 99%